Early allergen introduction overrides allergy predisposition in offspring of horses with Culicoides hypersensitivity - Simonin, Elisabeth M.; Torsteinsdóttir, Sigurbjorg; Svansson, Vilhjálmur; Björnsdóttir, Sigríður; Freer, Heather; Tarsillo, Justine; Wagner, Bettina (Frontiers in Immunology, 2025)
IntroductionThe origins of allergy are both genetic and environmental. We performed a full-sibling study to determine the role of early-in-life or delayed allergen introduction on Culicoides hypersensitivity development in a cohort with history of an allergic phenotype and Culicoides hypersensitivity. IgE-mediated allergies naturally develop in many mammalian species, and we used a horse model of allergy called Culicoides hypersensitivity. Culicoides hypersensitivity is a seasonal, recurrent, IgE-mediated allergy caused by the salivary proteins of biting Culicoides midges.MethodsThe study included four cohorts that lived together in the same environment, only differing in the timing of allergen exposure and the transfer of allergen-specific maternal antibodies. The parent cohort was first exposed to allergens in adulthood, and each full-sibling cohort was first exposed to allergen either in puberty or at birth. All full-siblings had at least one allergic parent with an allergic phenotype, suggesting a predisposition to develop allergy. Allergen-specific IgE and IgG isotypes were measured before and after exposure to Culicoides to determine whether maternal-acquired allergen-specific antibodies influenced the rate of Culicoides hypersensitivity development. All four cohorts were followed for at least nine years of allergen exposure.ResultsThe rate of allergy development was inversely related to the timing of allergen exposure where introduction in adulthood led to the highest rate of allergy development (62.5%), a moderate allergy rate was found for introduction during adolescence (21.4%), and no individuals exposed at birth developed Culicoides hypersensitivity. In addition, exposure to maternally-acquired allergen-specific IgE and IgG did not influence the rate of allergy development in the cohorts exposed to allergen at birth.DiscussionWe provide strong evidence in a full-sibling study that early-in-life allergen exposure, independent of maternal allergen-specific immunoglobulin, prevents Culicoides hypersensitivity development in individuals born to parents with an allergic phenotype.